A benchmark comparison of CRISPRn guide-RNA design algorithms and generation of small single and dual-targeting libraries to boost screening efficiency - Lukasiak, Sebastian; Kalinka, Alex; Gupta, Nikhil; Papadopoulos, Angelos; Saeed, Khalid; McDermott, Ultan; Hannon, Gregory James; Ross-Thriepland, Douglas; Walter, David (BMC genomics, 2025)
Genome-wide CRISPR sgRNA libraries have emerged as transformative tools to systematically probe gene function. While these libraries have been iterated over time to be more efficient, their large size limits their use in some applications. Here, we benchmarked publicly available genome-wide single-targeting sgRNA libraries and evaluated dual targeting as a strategy for pooled CRISPR loss-of-function screens. We leveraged this data to design two minimal genome-wide human CRISPR-Cas9 libraries that are 50% smaller than other libraries and that preserve specificity and sensitivity, thus enabling broader deployment at scale.